Effects of Date Seed (Phoenix dactylifera) Extract in an Animal Model of Diabetes Mellitus - Refaat, Sara (AUC Knowledge Fountain, 2023)
Diabetes mellitus is a chronic illness and a global epidemic. The commercial diabetic medicines available are expensive and have several adverse effects. Alternative natural products are still being sought for. Date seeds ( Phoenix dactylifera) are either thrown away as garbage or utilized as animal feed. The use of seed extract as an alternative therapy for diabetes offers a cost-effective and all-natural method for managing the disease. Methods Sprague dawley rats were randomly distributed into groups with a sample size of 4 rats per group. Date seed powder was boiled producing a 10% date seed extract which was administered in 10ml daily doses to each rat. Date seed extract was analyzed by high resolution UPLC-MS. Intraperitoneal Streptozocin injection was administered for diabetes induction at a concentration of 75mg/kg in sodium citrate buffer (pH 4.5). Diabetes was confirmed one week post injection with diabetic rats having a blood glucose above 250 mg/dL. Samples were collected biweekly for blood glucose and weight measurements. Stool pellets were flash frozen in liquid nitrogen and stored for sequencing. PowerSoil Kit was used for DNA extraction and further extraction used for Illumina 16s rRNA. QIIME2 and GraphPad Prism were used for bioinformatic and statistical analysis, respectively. Packages such as dada2, filterAndTrim, phyloseq in R and ggplot2 in R were used. Results Date seed extract had antidiabetic and antioxidant effects in rats, the diabetic group that received date seed extract showing a high prevalence of anti-diabetic and antioxidant benefits. The hypothesis was supported by the stark contrasts between the commercial remedy and the date seed extract. The blood glucose levels of the date seed group were 184.7 mg/dL, which was higher than the control group (159.7mg/dL), and lower than both the metformin and the diabetic untreated group with blood glucose levels of 271 mg/dL and 452.3 mg/dL respectively. Similar trends applied to oxidative stress tests, liver and kidney function tests. The gut microbiome composition also revealed differences between the samples, with an increase in diversity and abundance of beneficial bacteria in the normal and date seed extract group and a decrease in diversity in the commercial treatment and the negative control group. This information gave us insight into the dysbiosis in the gut microbiome caused by the disease as well as the changes caused by both the commercial treatment and the date seed treatment. 2 Conclusion This study sheds light on the usage of date seed extract as a diabetic treatment alternative and raises the prospect of additional research into the effects of date seed extract in human subjects to confirm its efficacy when used in place of conventional diabetic therapies.